Investigating the Influence of Brand Image and Promotional Strategies on Ruangguru’s Purchase Decisions - Syahputri, Natasya Aulia; Puspita, Afilia Teyja; Rifaldi, Muhamad Raihan; Abdullah, Muhammad (Masyrif : Jurnal Ekonomi, Bisnis dan Manajemen, 2025)
This study aims to examine the influence of brand image and promotional strategies on consumer purchase decisions regarding the Ruangguru online tutoring platform. As a pioneer in Indonesia's edtech industry with over 17 million users, Ruangguru faces challenges in maintaining customer loyalty and attracting new users amidst increasing competition. The main issue addressed is how edtech companies can optimize brand perception and promotional effectiveness to drive consumer purchase decisions. This research adopts a quantitative approach using a census method, involving 77 Ruangguru users in the Kebon Jeruk area, West Jakarta. The data were analyzed using descriptive and inferential statistics with the assistance of SPSS version 25. The results indicate that brand image and promotion significantly affect purchase decisions, with a combined contribution of 74.3%. Ruangguru’s brand image is perceived positively, particularly in terms of popularity, although brand recognition still requires reinforcement. In terms of promotion, target accuracy is rated favorably, but frequency needs improvement. Furthermore, the indicator of need recognition in purchase decisions was identified as the weakest aspect, indicating a lack of consumer awareness regarding the importance of the service. These findings support the theory that purchase decisions are not only directly influenced by brand image and promotion but also mediated by elements such as brand awareness and perceived need urgency. The practical implication of this study encourages Ruangguru to enhance brand visibility and market education through consistent digital promotion and need-based strategies. The study also recommends further research with broader geographic coverage and a focus on consumers’ psychographic characteristics.